"The Influence of Culture on the Disposition Effect" Arab Culture Experiment - Hassan, Hisham (2013)
Why do some investors manage their investments portfolios in a way where they “hold losers too long and sell winners too soon?” The phenomenon derived from this behaviour is labelled the disposition effect (DE). Many scholars and academics around the world have conducted several studies that aim to investigate this behaviour and discover the drivers behind it. In previous studies the DE has been attributed to drivers such as cognitive dissonance, regret theory, biases in return expectations, and the prospect theory. However, some scholars argue that such explanations for this behaviour are non-satisfactory, especially when they are not supported by empirical evidence. Therefore, two of my MBA colleagues and I decided to research this topic further in ways that expound why most individuals exercise different degrees of the DE. During our research, we noticed that there are no studies conducted in regards to culture being a key driver to the disposition effect. Former studies that researched the DE causes did not study culture exclusively as a primary factor. Therefore, we decided to research this area and conduct an experiment across three cultures ‘Arab, Indian, and Chinese’, in order to observe the influence of culture on the DE. In this paper, I will discuss and critique all the processes that I went through while conducting my portion of this project in Palestine, where I was testing for the Arab culture degree of DE. The experiment itself and the challenges faced during it setup and commencement phases will be also outlined in this paper. Likewise, results obtained from the Palestine experiment and the demographics concerning the sample of 30 students involved will also be analysed. Our study revealed that the Palestine sample tested exercised a degree of DE that ranges between -0.5 and 1. It also showed that on average females tend to exhibit a higher degree of DE on both the positive and negative side. I believe that these findings are tied to the social and business culture of the Palestinian people. This argument among many others will be later investigated within the results discussion section of this paper. Also, Palestine’s social and business culture will be among the topics briefly discussed to help understand its association with the results obtained.